2017
DOI: 10.1007/s00380-017-1075-3
|View full text |Cite
|
Sign up to set email alerts
|

Early and late outcomes after open ascending aortic surgery: 47-year experience in a single centre

Abstract: The aims of the study are to describe the long-term survival of patients undergoing primary open ascending aortic surgery and to portray the evolution of aortic surgery during six decades in a single centre. Included were all 614 patients who underwent primary ascending aortic surgery in 1968–2014 at one Nordic university hospital. Patients were identified and data were collected from patient records and surgical logs. Mortality data were acquired from the national registry. Median follow-up was 11.2 years usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
0
14
0
2
Order By: Relevance
“…The existing literature often implicates the aforementioned non-surgical characteristics as prognostic factors for late mortality, but on the other hand age and the comorbidity burden of the patients (mainly atherosclerosis) is also important for longterm survival in contemporary single-centre and multicentre series. Long-term postoperative survival after ATAAD repair is satisfactory and has improved in recent years: 84-85% at 5 years [9,62,109,110], 64-68% at 10 years [31,109,111,8], and up to 38% at 30 years [110].…”
Section: Outcome and Long-term Follow-upmentioning
confidence: 98%
“…The existing literature often implicates the aforementioned non-surgical characteristics as prognostic factors for late mortality, but on the other hand age and the comorbidity burden of the patients (mainly atherosclerosis) is also important for longterm survival in contemporary single-centre and multicentre series. Long-term postoperative survival after ATAAD repair is satisfactory and has improved in recent years: 84-85% at 5 years [9,62,109,110], 64-68% at 10 years [31,109,111,8], and up to 38% at 30 years [110].…”
Section: Outcome and Long-term Follow-upmentioning
confidence: 98%
“…Moreover, some studies [6,8,[11][12][13] have described the long-term survival of patients undergoing ascending aortic surgery. But these results, without comparing them with the general population of the same territory, provide little information since the life expectancy of any group depends on a collection of environmental and socio-economic factors of the territory where they reside.…”
Section: Introductionmentioning
confidence: 99%
“…Third, the information on the severity of thoracic aorta disease was lacking and may have affected postoperative patient outcome. Although a study suggested that the surgical indication for aorta surgery (dissection/ruptured aneurysm vs. intact aneurysms) had little effect on longterm mortality for 30-day survivors [28], another study suggested that in-hospital mortality seems to be worse in patients with ruptured thoracic aortic aneurysms compared to patients with intact thoracic aortic aneurysms [29]. Fourth, individual surgeon volume was not analyzed.…”
Section: Discussionmentioning
confidence: 99%